Geographical isolation and restricted gene flow drive speciation of Aegla singularis (Decapoda, Anomura, Aeglidae) in southern South America - Loretán, Gisela (2019)
Geographical isolation is a key element in allopatric speciation. If gene flow is interrupted for long enough by geographical barriers, populations can evolve independently and eventually form distinct species. Aegla singularis provides an ideal model to study this process due to the characteristics of the geographical area that it occupies and its limited dispersal ability. Aegla singularis inhabits streams of the Uruguay and Paraná River basins in the Neotropical region of South America. The basins are separated by the Sierra Central Mountains. Here we studied the speciation of A. singularis resulting from geographical isolation by using molecular and morphometric data. Individuals of A. singularis were analysed using geometric morphometrics and genetic data (COII and EFα1). We found significant differences in shape and genetics between A. singularis populations from the two basins. These differences suggest ongoing divergence due to restricted gene flow caused by the geographical barrier of the Sierra Central Mountains, indicating that the populations of the Parana and Uruguay River slopes are undergoing divergence.